ANALISIS BIAYA AKTIVITAS PRODUKSI RIBBED SMOKED SHEET UNTUK MENCAPAI EFISIENSI DENGAN PENDEKATAN METODE ACTIVITY BASED MANAJEMENT (Studi Kasus pada PT. Perkebunan Nusantara VII (Persero) Unit Musi Landas) - Ghozali, Rosalina (BALANCE Jurnal Akuntansi dan Bisnis, 2016)
This study included descriptive study to determine the cost aktivitas.Penelitian is trying to do the classification between activity value-added and non-value-added activities based on PT ABM method. Plantation Nusantara VII (Persero) Landas. Data Musi units used are primary data and secondary data. Data collection methods used were observation and data used dokumentasi.Analisis qualitative analysis and kuantitatif.Teknik analysis used by using data reduction, data presentation related to production activities and draw conclusions / verification.The results showed that there is no value-added activity for the company which is the removal of fumes second home, and penyimpana in warehouses in addition to the pressing. The activities are not value-added will certainly lead to their costs is not value-added, by implementing Activity Based Management (ABM) companies can save up to 3.3%. Therefore, companies need to implement Activity Based Management to eliminate activities that are not value-added, so that the production cost efficiency will be achieved.